PREPARATION, IDENTIFICATION AL (III) AND SELECTIVE ADSORPTION BY IMPRINTING POLYMER IN WATER IN BAGHDAD - G. S. Hassoon,; Y. K. Al-Bayati, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research aimed to form a molecularly imprinted polymer by adding aluminum ion at the first step were to the allyl bromide monomer resulted was formation using bulk polymerization. To acquire the highest adsorption capacity, molar ratios of template, monomer, and cross-linking agent, as well as solvents and multiple monomers, were investigated. Scanning electron microscopy (SEM) was used to analyze the produced aluminum. the maximum adsorption capacity of Al-IIP were 0.1531 µmol/g and 0.2362 µmol/g respectively. aluminum adsorption followed a Langmuir isotherm model. Solid-phase extraction (SPE) syringe packed with ionic imprinted polymers (IIP) were used to selective separation and preconcentration for aluminum (III) ion from aqueous solutions to determine the aluminum by flame atomic absorption spectroscopy (FAAS).